Multiple Pristionchus pacificus genomes reveal distinct evolutionary dynamics between de novo candidates and duplicated genes - Prabh, Neel; Rödelsperger, Christian (Genome Research, 2022)
The birth of new genes is a major molecular innovation driving phenotypic diversity across all domains of life. Although repurposing of existing protein-coding material by duplication is considered the main process of new gene formation, recent studies have discovered thousands of transcriptionally active sequences as a rich source of new genes. However, differential loss rates have to be assumed to reconcile the high birth rates of these incipient de novo genes with the dominance of ancient gene families in individual genomes. Here, we test this rapid turnover hypothesis in the context of the nematode model organism Pristionchus pacificus. We extended the existing species-level phylogenomic framework by sequencing the genomes of six divergent P. pacificus strains. We used these data to study the evolutionary dynamics of different age classes and categories of origin at a population level. Contrasting de novo candidates with new families that arose by duplication and divergence from known genes, we find that de novo candidates are typically shorter, show less expression, and are overrepresented on the sex chromosome. Although the contribution of de novo candidates increases toward young age classes, multiple comparisons within the same age class showed significantly higher attrition in de novo candidates than in known genes. Similarly, young genes remain under weak evolutionary constraints with de novo candidates representing the fastest evolving subcategory. Altogether, this study provides empirical evidence for the rapid turnover hypothesis and highlights the importance of the evolutionary timescale when quantifying the contribution of different mechanisms toward new gene formation.
10.1101/gr.276431.121